The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/gt.2013.81
|View full text |Cite
|
Sign up to set email alerts
|

The effect of helper epitopes and cellular localization of an antigen on the outcome of gene gun DNA immunization

Abstract: In DNA vaccination, CD4(+) T-cell help can be enhanced by fusion of a gene encoding an immunization protein with a foreign gene or its part providing T(h) epitopes. To study the effect of helper epitope localization in a protein molecule, the influence of the vicinity of the helper epitope, and the impact of chimeric protein cellular localization, we fused the helper epitope p30 from tetanus toxin (TT, aa 947-967) with the N- or C-terminus of the mutated E7 oncoprotein (E7GGG) of human papillomavirus type 16, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Several reports indicated that Th epitopes are capable of increasing the immunogenicity of CTL epitope-based vaccines, 34 and, as such, some universal Th epitopes were previously incorporated into such vaccines. 34,35 In this work, Th epitopes were included as part of the multi-epitope vaccine to induce better immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports indicated that Th epitopes are capable of increasing the immunogenicity of CTL epitope-based vaccines, 34 and, as such, some universal Th epitopes were previously incorporated into such vaccines. 34,35 In this work, Th epitopes were included as part of the multi-epitope vaccine to induce better immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In this work, Th epitopes were included as part of the multi-epitope vaccine to induce better immune responses. In contrast other studies, HIV-1-specific Th epitopes, rather than universal Th epitopes, were chosen for 2 reasons.…”
Section: Discussionmentioning
confidence: 99%
“…31 Cellular localization of the Aurka protein was changed by the sorting sequences of the LAMP-1 protein that have been published to enhance immunogenicity of other antigens. 31 Cellular localization of the Aurka protein was changed by the sorting sequences of the LAMP-1 protein that have been published to enhance immunogenicity of other antigens.…”
Section: Discussionmentioning
confidence: 99%
“…This combined immunotherapy significantly inhibited the growth of TC-1induced tumors, but only when a single dose of anti-CD25 was applied (Fig. 31 Similar to the PADRE.mutAurka gene in preventive immunization, the PADRE.E7GGG gene reduced tumor growth only in combination with a single anti-CD25 dose (Fig. In therapeutic immunization against TC-1 cells, when the PADRE.mutAurka DNA vaccine was applied 3, 7, and 10 days after TC-1 inoculation and antibody against CD25 was injected on days of immunization or 2 days before TC-1 inoculation, DNA vaccination alone or combined with anti-CD25 did not influence tumor growth (Fig.…”
Section: Depletion Of Cd25 + Cells Enhanced the Efficacy Of Dna Vaccimentioning
confidence: 93%
See 1 more Smart Citation